Estudio sistemático de las primeras ocupaciones humanas en la quebrada de Chalán; Revisión, histórica, arqueológica y del paisaje ocupado - Bonifaz Herrera, Lisette Victoria (2023)
The present research work addresses as its main theme the realization of a historical, archaeological and landscape review related to the first human occupations in the Quebrada de Chalán, which resulted in a rereading of the sociocultural issues of these populations, favoring the strengthening and rescue of the Chimboracense regional local history. The Chalán ravine is located between two rural parishes of the Riobamba canton, Licto e Punín, Chimborazo province, corresponding to a fossiliferous deposit known as an important geological deposit that keeps important material evidence of the paleo-fauna characteristic of the Pleistocene in its layers. of South America, as well as, the presence of remnant human fossils was evidenced in the context of their material culture or materiality, which undoubtedly speak of the oldest occupations of the Chimboracense territory so far evidenced. In the development of this qualitative research, the research techniques and instruments that were used for the collection of information are the notebook,worksheets and analysis of the documents which facilitated the work to know the human remains and the associated material culture that lay in the Chalán ravine, data collection has been somewhat difficult due to the lack of new investigations, to such an extent that the belonging of the ravine to the parishes of Punín and Licto and the veracity are currently under discussion. of the antiquity of this materiality.